PENGANGKATAN BAPAK ANGKAT BAGI CALON PENGANTIN LAKI-LAKI DALAM PERSPEKTIF HUKUM ISLAM (STUDI DI KECAMATAN BATHIN VIII) - Rinaldi; Hermanto Harun; Robiatul Adawiyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims: (1) To find out the practice of appointing adoptive fathers in the marriage procession in Bathin VIII Sub-district. (2) To determine the status of the position of the appointment of the adoptive father according to Islamic Law in Bathin VIII sub-district. (3) To find out the practice of adopting children according to Islamic Law in Bathin VIII Subdistrict. This research method is qualitative description with content analysis approach on juridical elmpiris. This approach can be explained as a legal research on how to apply and implement nullrmative legal regulations in real situations. The results of this study indicate that: (1) The process and practice of adopting a foster father in the customary society of Teluk Kecimbung emphasizes more on social and cultural functions, especially in maintaining good relations between the two families. This appointment is not related to the legal adoption of children in the context of Islamic law. (2) The status of the adoptive father according to Islamic law is not recognized as a guardian or a party with a certain legal position in the family. The role of the adoptive father in this custom is more in the nature of social relations in establishing good relations in the family and community. (3) The practice of appointing adoptive fathers according to Islamic law does not change a person's position in the Islamic family structure because this appointment is more symbolic in maintaining communication between families and solving social problems that arise, not as a legal family bond according to religion. The actualization of this custom is part of culture, custom, and the actualization of Islamic teachings through the tradition of appointing adoptive fathers, which has an important role for the community.